High rabies burden and low vaccination status among dogs inflicting bite in Addis Ababa: an urgent call for action - Sintayehu Abdella; Khogali Ahmed; Bienvenu Salim; Baye Ashenefe; Yimere Mulugeta; Endalkachew Girma; Mesefin Aklilu; Abebe Getachew; Gutu Kitila; Garuma Getahun; Endalkachew Berihanu; Ibsa File; et al. (Journal of Infection in Developing Countries)
Introduction: Rabies remains a global threat, killing approximately 60,000 people every year. In Ethiopia, dogs are the main reservoir of the disease. Animals also estimate the burden of the disease.